Working from Home and COVID-19: The Chances and Risks for Gender Gaps - Melanie Arntz; Sarra Ben Yahmed; Francesco Berlingieri (Intereconomics, 2020)
As the COVID-19 pandemic causes a record number of people to work from home, this disruptive event will likely have a long-lasting impact on work arrangements. Given existing research on the effects of working from home on hours worked and wages, an increased availability of working from home may provide a chance for women to catch up with their male counterparts. Yet, the need to simultaneously care for children during the COVID-19 lockdown may also revive traditional gender roles, potentially counteracting such gains. We discuss the likely effects of the COVID-19 pandemic on gender gaps in the labour market and at home in light of recent empirical findings and novel statistics on the heterogeneous structure of work arrangements among couples. We construct a novel teleworkability index that differentiates between fully teleworkable, partly teleworkable and on-site jobs and find that in about a third of households the COVID-19 shock is likely to induce shifts in the intra-household allocation of tasks from mothers to fathers.
Keywords: 330; Coronavirus; Epidemie; Telearbeit; Geschlechterunterschiede